Occurrence of Human Defensins and S100 Proteins in Head and Neck Basal Cell Carcinoma (BCC) Entities: hBD3 and S100A4 as Potential Biomarkers to Evaluate Successful Surgical Therapy - Eva Dröge; Rainer Probstmeier; Matthias Wenghoefer; Jochen Winter (MDPI AG, 2023)
Background: The goal of this study is the identification of potential marker molecules for characterizing different basal cell carcinoma entities, to help improve clinical decisions for surgical resection therapy. Methods: Three different entities, sclerodermiform, solid and superficial basal cell carcinomas, were subjected to immunohistochemical microscopy and histomorphometric analyses for human α- (DEFA1/3; DEFA4) and β-defensins (hBD1/2/3) and special S100 proteins (S100A4/7/8/9). Thirty specimens of the three entities were evaluated. Analyses were performed by comparing tissue and cellular localization and staining intensities of tumorous with non-tumorous areas. Staining intensities were semiquantitatively examined by using an RGB-based model. Results: Human defensins are present in all three entities of basal cell carcinomas. They all show cytoplasmic immunostaining in cells of the epithelium, stroma and tumor. Notably, human β-defensin3 is accumulated in the cell nuclei of sclerodermiform and superficial basal cell carcinomas. S100A4 and A7 are undetectable in tumor regions. However, S100A4 occurs in cancer-associated stroma cells with nuclear staining in superficial basal cell carcinomas. Conclusion: Two candidates, namely hBD3 and S100A4, might be used as potential clinical tools for evaluating successful surgical resection therapy to avoid aesthetic and functional facial deformation.